Quantifying confidence in the reporting of metabolic biotransformations. Issue 7 (July 2017) - Ponting, David J.; Murray, Ernest; Long, Anthony
Highlights: A metric for quantifying the certainty in the formation of metabolites is proposed. The necessary set of analytical techniques for maximal confidence is discussed. There are always intermediate metabolites, whose formation can only be inferred. Abstract : How confident can we be in the assignment of metabolite structures? Are the analytical techniques used sufficient to support hypotheses about what is being formed? In this Feature, we discuss the results of an extensive survey into the analytical techniques used, and their value in the characterisation of metabolites. The survey covers the structures of over 16 000 metabolites formed from 1732 query compounds, covering over 35 years of the literature and a variety of journals. The value of different characterisation techniques is considered, alongside or in the absence of synthetic standards. The changes in analytical techniques used over time are briefly considered, and a metric for the confidence that a claimed metabolite has been confirmed is proposed.